Challenges Faced By Shariah Supervisory Board Members: A Case Study in One Islamic Bank - Soufran Yusuf; Romli SA; Muhammad Rusdi (Al-Buhuts, 2023)
The purpose of this study was to explore the challenges faced by members of the Shariah Supervisory Board and how they overcame the challenges in carrying out their functions in Islamic banks. This research was a case study and three members of the Shariah Supervisory Board of one of the regional Islamic banks in South Sumatra were selected as research participants by using total sampling. This research was conducted qualitatively using case study. This research used semi-structured interviews as a data collection method. Then, the data were analyzed using the interactive analysis model suggested by Miles and Huberman. The interview results revealed the challenges faced by the Shariah Supervisory Board members were related to competence, independence, professionalism, integrity and technology. The results also revealed how members of the Shariah Supervisory Board overcame these challenges.